Let \(\alpha(p)\) denote the least positive subscript, where \( p|F_{\alpha(p)}\). A prime p is a Wall Sun Sun prime if
\( \alpha(p^2) = \alpha(p) \).
Then FFα(p2)=FFα(p) , where Fp2∣FFα(p) and α(FFα(p2))=α(FFα(p)). Let n=p1e1p2e2⋯pkek=Fα(p). Then
(i)
If pk=p,ek≥2, then α(Fp1e1Fp2e2⋯Fpkek)=α(Fp1e1Fp2e2⋯Fpk), for n=p1e1,n=p1e1p2e2⋯pkek, where 2∦n, or 2∤n.
If p1=p,e1≥2, then α(Fp1e1Fp2e2⋯Fpkek)=α(Fp1Fp2e2⋯Fpkek), for n=p1e1,n=p1e1p2e2⋯pkek, where 2∦n, or 2∤n.
If pi=p,ei≥2, then α(Fp1e1⋯Fpiei⋯Fpkek)=α(Fp1e1⋯Fpi⋯Fpkek), for n=p1e1,n=p1e1p2e2⋯pkek, where 2∦n, or 2∤n.
(ii)
If pk=p,ek≥2, then α(F2Fp2e2Fp3e3⋯Fpkek)=α(F2Fp2e2Fp3e3⋯Fpk), for n=p1e1,n=p1e1p2e2,n=2p2e2p3e3⋯pkek, where 2∥n.
If p2=p,e2≥2, then α(F2Fp2e2Fp3e3⋯Fpkek)=α(F2Fp2Fp3e3⋯Fpkek), for n=p1e1,n=p1e1p2e2,n=2p2e2p3e3⋯pkek, where 2∥n.
If pi=p,ei≥2, then α(F2Fp2e2⋯Fpiei⋯Fpkek)=α(F2Fp2e2⋯Fpi⋯Fpkek), for n=p1e1,n=p1e1p2e2,n=2p2e2p3e3⋯pkek, where 2∥n.
(iii)
If p2=p,e2≥2, then α(F2Fp2e2)=α(F2Fp2), for n=2p2e2, where 2∥n.
(iv)
If p1=p,e1≥2, then α(Fp1e1)=α(Fp1), for n=p1e1, where 2∦n, or 2∤n.
We know that:
If d∣n, then Fd∣Fn, for d≤n,n≥1.
If Fd∤Fn, then d∤n, for d≤n,n≥1.
α(Fn)=n, for n=2.
α(FFn)=Fn, for n=2,n=3.
α(ϕn)=α(Fn), for n=2.
ϕn=∏d∣nFdμ(n/d), for all divisors d of n. {T.M. Apostol 1976}
βn=∏d∣nFd−μ(n/d), for proper divisors d of n.
Fn=βnϕn.
We can prove Fpiei∤FFα(pi), for λ≥ei≥2. Then piei∤Fα(pi), for λ≥ei≥2.
gcd(Fp1e1,Fp2e2)=Fgcd(p1e1,p2e2)=F1=1, for distinct primes p1,p2,e1≥1,e2≥1. {E. Lucas}
Let [a,b] denote the least common multiple of a and b. Then α([a,b])=[α(a),α(b)]. {D. W. Robinson 1963}
(i) α(Fp1e1Fp2e2⋯Fpkek)=α([Fp1e1,Fp2e2,...,Fpkek])=[α(Fp1e1),α(Fp2e2),...,α(Fpkek)]=[p1e1,p2e2,...,pkek]=(p1e1p2e2⋯pkek)=n, for n=p1e1,n=p1e1p2e2⋯pkek, where 2∦n, or 2∤n.
(ii) α(F2Fp2e2Fp3e3⋯Fpkek)=α([F2,Fp2e2,Fp3e3,...,Fpkek])=[α(F2),α(Fp2e2),α(Fp3e3),...,α(Fpkek)]=[1,p2e2,p3e3,...,pkek]=(p2e2p3e3⋯pkek)=2n, for n=p1e1,n=p1e1p2e2,n=p1e1p2e2p3e3⋯pkek, where 2∥n.
(iii) α(F2Fp2e2)=α([F2,Fp2e2])=[α(F2),α(Fp2e2)]=[1,p2e2]=(p2e2)=2n, for n=2p2e2, where 2∥n.
(iv) α(Fp1e1)=α([Fp1e1])=[α(Fp1e1)]=[p1e1]=(p1e1)=n, for n=p1e1, where 2∦n, or 2∤n.
If pλ∥Fα(p), then Fpλ∣FFα(p), for λ≥2. According to the 4 proof points above, either
α(Fp1e1Fp2e2⋯Fpkek)=α(Fp1e1Fp2e2⋯Fpk)=(p1e1p2e2⋯pkek)=(p1e1p2e2⋯pk), for pk=p,λ≥ek≥2, or
α(Fp1e1Fp2e2⋯Fpkek)=α(Fp1Fp2e2⋯Fpkek)=(p1e1p2e2⋯pkek)=(p1p2e2⋯pkek), for p1=p,λ≥e1≥2, or
α(Fp1e1⋯Fpiei⋯Fpkek)=α(Fp1e1⋯Fpi⋯Fpkek)=(p1e1⋯piei⋯pkek)=(p1e1⋯pi⋯pkek), for pi=p,λ≥ei≥2, or
α(F2Fp2e2Fp3e3⋯Fpkek)=α(F2Fp2e2Fp3e3⋯Fpk)=(p2e2p3e3⋯pkek)=(p2e2p3e3⋯pk), for pk=p,λ≥ek≥2, or
α(F2Fp2e2Fp3e3⋯Fpkek)=α(F2Fp2Fp3e3⋯Fpkek)=(p2e2p3e3⋯pkek)=(p2p3e3⋯pkek), for p2=p,λ≥e2≥2, or
α(F2Fp2e2⋯Fpiei⋯Fpkek)=α(F2Fp2e2⋯Fpi⋯Fpkek)=(p2e2⋯piei⋯pkek)=(p2e2⋯pi⋯pkek), for pi=p,λ≥ei≥2, or
α(F2Fp2e2)=α(F2Fp2)=(p2e2)=(p2), for p2=p,λ≥e2≥2, or
α(Fp1e1)=α(Fp1)=(p1e1)=(p1), for p1=p,λ≥e1≥2, which is absurd.
Does anyone have any comments, questions, suggestions, or corrections?
#NumberTheory
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
There are no comments in this discussion.